Association between landscape heritage elements and place attachment among visitors in Taiping Lake Garden, Perak, Malaysia - Abd Ghani, Nurul Hijrah (2015)
As commonly realized by most people, the priceless heritage is susceptible to deteriorate or destroyed by either natural phenomenon or human negligence. Henceforth, creating public awareness on this irreplaceable heritage is a necessity to ensure its continuous existence in the future. In the case of Taiping Lake Garden, Perak up to now there is still no study claimed that visitors are attached to the Lake Garden due to its heritage. Hence, this study aims to discover the association between landscape heritage elements and visitors’ attachment to Taiping Lake Garden since there is still a gap of knowledge on this association. It is mentioned that place functioning depends on individual meaning, activity and physical form. Therefore, it is important to explore the meaning of place for visitors because it contributes in understanding visitors’ attachment which later will be used to enhance the site. The objectives of this study are to document the landscape heritage elements and examine the influence of these heritage elements on visitors’ attachment.Ta iping Lake Garden was selected as the study site as it is one of the oldest gardens in Malaysia. The method employed is through archival study, interview and field observation for documenting the heritage elements found in Taiping Lake Garden. Meanwhile, a questionnaire survey is used to explore the influence of heritage elements on visitors’ attachment to Taiping Lake Garden. The results from the archival study, interview and field observation indicate that physical, non-physical and natural landscape elements are the landscape heritage elements of Taiping Lake Garden. While, the result of the surveys demonstrated that these heritage elements have influenced the visitors’ attachment to the place. This study will assist planners and designers to better understand the factors that influence visitors’ attachment and improve the current state of the park so more visitors will come to visit the site.